Women’s participation in local politics in Zimbabwe: the case of Chiwundura of Midlands province, 2000-2018. - Gijima, Fadzai (Midlands State University, 2019)
The study is a qualitative exposition of women participation in local politics in Zimbabwe. The study examines the efforts made to promote the participation of women in local politics in Chiwundura, the status of women and the challenges that militate against women participation. The case for the study is Chiwundura a rural area in the Midlands Province. The study covers the period 2000-2018. Qualitative data collection methods which include interviews and questionnaires were used. The study is guided by the radical feminist theory which purports that woman problems are caused by men. The study revealed that intervention programmes have been done to promote women participation in local politics. However it has been ascertained that the efforts have not yielded much because of the socio-cultural factors that shape the attitudes of people towards politics. The study has identified patriarchy, lack of financial resources, and lack of education, marriage, religious beliefs, and stereotypes among others as factors that militate against women participation in politics. Consequently the research revealed that whilst it is advantageous to have women in politics for sustainable development the number of women in politics in Chiwundura has remained minimal. The research recommends women to form pressure groups to educate women on ways used by men to oppress them and find ways to resist male dominance through inculcating an understanding of gender parity. It also recommends women to form their political parties and compete with men for political posts in their communities.